Juridical consequences of lending and borrowing agreements that are covered with the substance of buying and selling paid off ownership rights to land: - Charles Lungkang; Putu Dyatmikawati; Made Gde Subha Karma Resen (Universitas Bali Dwipa, 2023)
The position of the lending and borrowing agreement which is covered by the substance of the sale and purchase of paid off land ownership rights, in this case the position is based on an agreement or loan agreement between the parties which requires the borrowing party to pay off the debt after a certain period of time accompanied by payment of a number of rewards. Lending within a certain period of time set by the lender. The loan recipient pays off the loan, by returning the loan money. The position of the lending and borrowing agreement relates to freedom of contract, the parties can regulate the contents of the agreement as long as it is not prohibited by law and propriety and in the contract must fulfill the terms of the agreement. This position is born from the existence of an agreement between the two parties, namely the borrower and the lender, so with this agreement the loan agreement is binding on both parties, that is, the parties cannot cancel the loan agreement without the approval of the other party. If the loan agreement is canceled or terminated unilaterally, the other party can sue. After the money that is the object of the agreement has actually been handed over by the lender to the borrower, the borrower must or has the obligation to return the loan on time to the lender in accordance with the agreement in the agreement.